USING GAME IN IMPROVING STUDENTS’ VOCABULARY MASTERY - Siti Safura; Cut Mawar Helmanda (Jurnal Dedikasi Pendidikan, 2022)
This study was aimed at improving vocabulary mastery through games. It is to see whether game can improve students’ vocabulary mastery and to know the effectiveness of using game in teaching class. The participants of this study were 10 students and one English lecturer at University of Muhammadiyah Aceh. The data were obtained from questionnaires that distributed to students and interview one lecturer to add more information. In analyzing the data, this study applied the qualitative descriptive method. The result of this study reveals that the implementation of game in teaching learning process is effective in which it encourages students’ motivation and involvement during the learning process. Indeed, it becomes the relevant way for lecturer to improve students’ vocabulary mastery.